Pre-fracture quality of life predicts 1-year survival in elderly patients with hip fracture—development of a new scoring system. Issue 6 (June 2016) - Bliemel, C.; Sielski, R.; Doering, B.; Dodel, R.; Balzer-Geldsetzer, M.; Ruchholtz, S.; Buecking, B.
Abstract Summary Hip fractures are common in elderly people. Despite great progress in surgical care, the outcome of patients with hip fracture remains disappointing. This study determined four prognostic factors (lower ASA score, higher pre-fracture EQ-5D index, higher MMSE score, and female gender) to predict 1-year survival in patients with hip fracture. Introduction This study determined the prognostic factors for 1-year survival in patients with hip fracture. Based on these predictors, a scoring system was developed for use upon patients' admission to the hospital. Methods Hip fracture patients, aged ≥60 years, were prospectively enrolled. Upon admission, patients' sociodemographic data, type of fracture, American Society of Anesthesiologists (ASA) score, health-related quality of life scores (EQ-5D index) and Mini-Mental State Examination (MMSE) scores were recorded, among other parameters. Correlational analysis was performed on all potential variables to identify relevant predictor variables of 1-year survival. Univariate regression analysis was performed on all selected variables, followed by a multivariate analysis for variables that were significant in the univariate analysis. The final score was developed by converting the β-coefficients of each variable from the multivariate analysis into a scoring system. Results For 391 hip fracture patients, complete data were available at the time of the 1-year follow-up. In multivariate regression analysis, independent predictors of 1-year survival were lower ASA score, higher pre-fracture EQ-5D index, higher MMSE score, and female gender. The different variables were weighted according to their β-coefficient to build the prognostic score, which ranged from 0 to 10 points. The ROC curve for 1-year mortality after hip fracture showed an area under the curve of 0.74 (R 2  = 0.272; 95 % CI 0.68–0.79;p  < 0.001). Conclusions With only four instruments, the new score represents a useful tool for estimating 1-year survival in elderly patients with hip fractures. At present, the score is limited due to a lack of validation. A validation study is currently underway to prove its reliability.